Antioxidant enzyme status on rat after date seeds (Phoenix dactylifera) steeping treatment - ., Saryono; Rahmawati, Eni; ., Heryanto; Hapsari, Eti Dwi; Hidayat, Arif Imam (International Journal of Research in Medical Sciences, 2017)
Background: Free radicals can damage normal cells thereby accelerating aging. Endogen antioxidant enzymes play an important role in inhibiting the oxidation rate of free radicals. This study aimed to assess the effect of date seed steeping on the indigenous antioxidant enzymes status in rats induced by alloxan. Methods: This research used pre and post-test with control group design. A total of 30 rats were randomized to six groups. There were the treatment groups with different dosage of date seeds steeping (0.25; 0.5; 0.75; 1) g/kg, positive control group with vitamin C 1 g/kg per day and negative control group. Deglet Noor date seeds variant were cleaned and dried and was roasted and mashed. Examination of the glutathione peroxidase (GPx) and superoxide dismutase (SOD) activity were conducted in accordance of the research of Castenmiller et al., (1999). Data were analyzed by Anova and continued by post-hoc test. Results: The results showed that GPx and SOD levels increased significantly. There were differences in SOD and GPx activity between the groups after treatment of date seed steeping. Increasing of SOD activity in the group that was given date seed steeping dose of 0.75 g/kg and vitamin C as a positive control group was comparable. The GPx activity between treatment group of date seed steeping a dose of 1 g/kg is not significantly different from positive control group. Conclusions: Date Seeds (Phoenix dactylifera) steeping have potential to increase antioxidant enzyme states.